Inactivation of the Tricarboxylic Acid Cycle Aconitase Gene from Streptomyces viridochromogenes Tü494 Impairs Morphological and Physiological Differentiation - Schwartz, D. (American Society for Microbiology, 1999)
The tricarboxylic acid (TCA) cycle aconitase gene acnA from Streptomyces viridochromogenes Tü494 was cloned and analyzed. AcnA catalyzes the isomerization of citrate to isocitrate in the TCA cycle, as indicated by the ability of acnA to complement the aconitase-deficient Escherichia coli mutant JRG3259. An acnA mutant was unable to develop aerial mycelium and to sporulate, resulting in a bald phenotype. Furthermore, the mutant did not produce the antibiotic phosphinothricin tripeptide, demonstrating that AcnA also affects physiological differentiation.